Pengaruh Sales Promotion dan Kualitas Pelayanan Terhadap Minat Pembelian Ulang di Mediasi Variabel Kepuasan Konsumen (Survei pada Konsumen GrabBike Online di Kota Malang) - Muhammad Muiz; N. Rachma; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
AbstractThis study aims to (1) explain the direct effect of Sales Promotion Service Quality on Customer Satisfaction, (2) explain the effect of Sales Promotion and Service Quality on Repurchase Interests, (3) explain the effect of Customer Satisfaction on Repurchase Interests (4) explain the influence Direct Sales Promotion Service Quality for Repurchase Interests in Variable Mediation Customer Satisfaction. This type of research is explanatory research with a quantitative approach. The variables in this study consisted of Sales Promotion, Service Quality, Consumer Satisfaction, and Repurchase Interest. The population criteria in this study are consumers with a minimum age of 17 years, are in the city of Malang at the time of research, and have purchased GrabBike Online services in the Malang City area, especially Lowokwaru District, at least once. The sampling technique used was purposive sampling and the method of collecting data through a questionnaire directly (offline) to 116 respondents who fit the criteria of the population. Analysis of the data used is descriptive analysis and path analysis (path analysis) Kеywords: Sales Promotion, Service Quality, Re-purchase Intention, Customer Satisfaction